PFKM gene defect and glycogen storage disease GSDVII with misleading enzyme histochemistry - Auranen, Mari (Neurol Genet, 2015)
OBJECTIVE: To elaborate the diagnostic methods used as “gold standard” in one of the most common glycogen storage diseases (GSDs), Tarui disease (GSDVII). METHODS: Two siblings with disease suggestive of GSD underwent thorough clinical analysis, including muscle biopsy, muscle MRI, exercise tests, laboratory examinations, and whole-exome sequencing (WES). RESULTS: Both siblings had juvenile-onset exercise intolerance with cramping and infrequent myoglobinuria. Muscle biopsy showed extralysosomal glycogen accumulation, but because of normal phosphofructokinase histochemistry, GSDVII was thought to be excluded. However, WES revealed a causative homozygous PFKM gene defect, R39Q, in both siblings, establishing the diagnosis of GSDVII, which was confirmed by very low residual phosphofructo-1-kinase (PFK) enzyme activity in biochemical studies. CONCLUSIONS: We suggest that in patients with suspicion of GSD and extralysosomal glycogen accumulation, biochemical activity assay of PFK followed by molecular genetics should be performed even when enzyme histochemistry is normal.